(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article training of national wrestlers , development of agility and strength qualities , effective formation of sports skills as the most important foundation in training of wrestlers , exercises related to flexibility development , physical training, development of special action skills issues were discussed.